2014
DOI: 10.1504/ijwgs.2014.060260
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Web of Things: an analysis of the application semantics for the IoT moving towards the IoT convergence

Abstract: The Internet of Things (IoT) is being applied for stovepipe solutions, since it presents a semantic description limited to a specific domain. IoT needs to be pushed towards a more open, interoperable and collaborative IoT. The first step has been the Web of Things (WoT). WoT evolves the IoT with a common stack based on web services. But, even when a homogeneous access is reached through web protocols, a common understanding is not yet acquired. For this purpose, the Semantic Web of Things (SWoT) is proposed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(55 citation statements)
references
References 19 publications
0
54
0
1
Order By: Relevance
“…The Semantic Web of Things (SWoT) [72] paradigm is proposed for the integration of the Semantic Web with the WoT, for realizing a common understanding of the various entities which form the IoT. Recent research has concluded that semantic web technologies are a major driver for interoperability across heterogenous environments [73]. The literature uses semantic web technologies to achieve semantic interoperability by using standards or agreements on the format and meaning of data or in a dynamic way by using shared vocabularies either in a schema form and/or in an ontology-driven approach.…”
Section: Semantic Web Technologiesmentioning
confidence: 99%
“…The Semantic Web of Things (SWoT) [72] paradigm is proposed for the integration of the Semantic Web with the WoT, for realizing a common understanding of the various entities which form the IoT. Recent research has concluded that semantic web technologies are a major driver for interoperability across heterogenous environments [73]. The literature uses semantic web technologies to achieve semantic interoperability by using standards or agreements on the format and meaning of data or in a dynamic way by using shared vocabularies either in a schema form and/or in an ontology-driven approach.…”
Section: Semantic Web Technologiesmentioning
confidence: 99%
“…However, interoperability in the IoT concerns various layers of the communication stack. The advancements of integrating smart things in the various layers are labelled with Internet of Things (network layer), Web of Things (application layer) and Semantic Web of Things (a common description of things) [7]. Since the underlying layers adopted standard technologies of the web (such as HTTP/HTML), leveraging semantic web technologies for the IoT is a promising approach to converge heterogeneous data sources in a smart ecosystem [8].…”
Section: B Semantic Interoperability In the Iotmentioning
confidence: 99%
“…RDF provides a flexible approach to support and specify domain-dependent and independent vocabularies, and to define relations between terms from different vocabularies [7]. However, even though the vocabulary can be easily accessed, consumers must be able to understand the used vocabulary by the publisher, by either using the same or an aligned vocabulary.…”
Section: B Semantic Interoperability In the Iotmentioning
confidence: 99%
See 2 more Smart Citations